Easy And Efficient Methods of Conducting English Lessons for Children - Akobirova Kamola Malikovna; Esanova Nafosat Fakhriddinovna (Open Academia, 2023)
In this article , easy and effective ways to conduct English lessons for children , knowledge of foreign languages expands a person's worldview and makes him feel at home anywhere in the world, children's favorite pastime, outdoor games, interesting and logical assumption information about making games is given
Keywords: curriculum; reproductive; logical assumption; absolute level